Common causes of blindness and visual handicap in the west of Scotland. Issue 4 (April 1983) - Ghafour, I. M.; Allan, D.; Foulds, W. S.
Abstract : An analysis of blind registration forms was made to determine the commonest causes of blindness in the west of Scotland. It was found that the leading causes of blindness in order of frequency of incidence were senile macular degeneration, glaucoma, cataract, diabetic retinopathy, and myopic degeneration. Diabetic retinopathy was the leading cause of blindness among persons of working age.